Frequent small amplifications in the FMR-1 gene in fra(X) families: limits to the diagnosis of 'premutations'. Issue 11 (November 1992) - Macpherson, J N; Nelson, D L; Jacobs, P A
Abstract : In five of 40 fra(X) families reinvestigated using the new intragenic probe StB12.3, small amplifications of the DNA fragment appeared unexpectedly in addition to the mutations found in the probands. This suggests that enlargements of the FMR-1 gene detectable by Southern blotting using this probe must be present at an appreciable frequency in the general population. A proportion of these may be classifiable as 'premutations', or precursors of the much amplified, hypermethylated, and somatically unstable fragment associated with the fragile X syndrome, while others will merely represent stable polymorphisms in fragment length. Hence, accurate diagnosis of some fra(X) carriers will depend upon a more precise measurement of insert size than is currently provided by the newly available molecular probes.